(untitled) (Costos y Gestión, 2021)
Following the fundamental role that Civil Society Organizations have through Non-formal education in Argentina and their existing relationship to the corporate responsibility, this paper aims at a first approach not only to how these organizations educate, but also how they manage, measure and control the total number of resources to pursue their social goal. But in this universe of capital movements registered according to legal, accountable and even internal regulations specific to the legal structure adopted by each of these Civil Society Organizations, an ‘invisible’ universe is created, which we call ‘the invisible accounting’. This universe includes all those capital movements that for any reason are not registered, measured neither controlled, but they are related to the corporate social responsibility of social actors where the Non-formal education takes place.